2018
DOI: 10.1098/rstb.2016.0444
|View full text |Cite
|
Sign up to set email alerts
|

In medio stat virtus : unanticipated consequences of telomere dysequilibrium

Abstract: The integrity of chromosome ends, or telomeres, depends on myriad processes that must balance the need to compact and protect the telomeric, G-rich DNA from detection as a double-stranded DNA break, and yet still permit access to enzymes that process, replicate and maintain a sufficient reserve of telomeric DNA. When unable to maintain this equilibrium, erosion of telomeres leads to perturbations at or near the telomeres themselves, including loss of binding by the telomere protective complex, shelterin, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 144 publications
1
11
0
Order By: Relevance
“…Somewhat counterintuitively, recent work suggests that telomerase could in fact bind reversed telomeric replication forks in mouse cells deficient for RTEL1 and in this context induce catastrophic telomeric repeat loss ( Margalef et al, 2018 ). While the absence of active telomerase in human somatic cells is an important mechanism to avoid uncontrolled proliferation, it has also been demonstrated that preventing excessive telomere elongation and regulating telomere length at a certain homeostatic level is important for maintaining the functional state of telomeres [reviewed in ( Harrington and Pucci, 2018 )]. It is therefore tempting to speculate that in certain multicellular organisms, repair of telomeric replication fork collapse by telomerase indeed has been evolutionarily counter-selected.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat counterintuitively, recent work suggests that telomerase could in fact bind reversed telomeric replication forks in mouse cells deficient for RTEL1 and in this context induce catastrophic telomeric repeat loss ( Margalef et al, 2018 ). While the absence of active telomerase in human somatic cells is an important mechanism to avoid uncontrolled proliferation, it has also been demonstrated that preventing excessive telomere elongation and regulating telomere length at a certain homeostatic level is important for maintaining the functional state of telomeres [reviewed in ( Harrington and Pucci, 2018 )]. It is therefore tempting to speculate that in certain multicellular organisms, repair of telomeric replication fork collapse by telomerase indeed has been evolutionarily counter-selected.…”
Section: Discussionmentioning
confidence: 99%
“…They shorten with the number of cell divisions in vitro as well as in response to oxidative stress and critically short telomeres trigger a DNA damage response that leads to replicative senescence or apoptosis 3 5 . In the last decade or so, measures of average telomere length (TL) taken from blood samples have emerged as an exciting biomarker of health across disciplines including biomedicine, epidemiology, ecology and evolutionary biology 6 8 . Considerable among- and within-individual variation in TL has been observed, with a general pattern of rapid telomere attrition during early life and a plateau or slower decline thereafter 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, roles distal to the telomere have been described for the telomere shelterin subunit, Rap1, in mice and in budding yeast (Marión et al, 2017;Platt et al, 2013;Song and Johnson, 2018;Vaquero-Sedas and Vega-Palas, 2018). There are other consequences for cell fate beyond senescence, as telomere dysfunction is known to impair stem cell differentiation in numerous contexts (Harrington and Pucci, 2018). For example, eroded telomeres in mESCs impair their ability to fully consolidate a differentiated phenotype in response to all-trans retinoic acid (ATRA) (Pucci et al, 2013).…”
Section: Introductionmentioning
confidence: 99%